(untitled) (Texas Journal of Medical Science, 2024)
Each of these methodologies has its strengths and can be effective depending on the learners’ needs, contexts, and goals. Many teachers adopt a blended approach, incorporating elements from multiple methodologies to create a dynamic and responsive learning environment. The key is to remain flexible and attuned to the needs of the students, fostering an engaging and supportive atmosphere for language acquisition